2015
DOI: 10.1016/j.juro.2014.08.085
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Following Radical Cystectomy: Significant Predictors, Comparison of Different Anticoagulants and Timing of Events

Abstract: Venous thromboembolism remains a significant complication of open radical cystectomy. Using an in-house, heparin based anticoagulation protocol consistent with current AUA (American Urological Association) guidelines has not decreased the rate of venous thromboembolism compared to historical warfarin use. On closer evaluation most venous thromboembolism cases in our population occurred after discharge home. Future studies are needed to establish the benefits of extended duration venous thromboembolism prophyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 31 publications
2
33
1
1
Order By: Relevance
“…An incidence of 1.8% recorded in this study is comparable with other contemporary series which report VTE rates varied between 0.4 and 5.5% in major urologic oncology surgery [2-5]. We also found that radical cystectomy confers a greater risk of VTE compared to radical cystectomy, again in keeping with published data [6][7][8][9][10][11][12][13]. The probable reason for this is the fact that patients undergoing radical cystectomy have greater risk factors for VTE compared to those undergoing radical prostatectomy.…”
Section: Discussionsupporting
confidence: 91%
“…An incidence of 1.8% recorded in this study is comparable with other contemporary series which report VTE rates varied between 0.4 and 5.5% in major urologic oncology surgery [2-5]. We also found that radical cystectomy confers a greater risk of VTE compared to radical cystectomy, again in keeping with published data [6][7][8][9][10][11][12][13]. The probable reason for this is the fact that patients undergoing radical cystectomy have greater risk factors for VTE compared to those undergoing radical prostatectomy.…”
Section: Discussionsupporting
confidence: 91%
“…Predictors of high risk for VTE development identified include: elevated BMI, surgical margins, type of diversion and length of hospital stay. 48 Alberts et al reported a similar rate, 5.5%, among 2065 patients within 30 days of surgery. This group noted lower rates in patients undergoing radical/partial nephrectomy (0.7%) and radical prostatectomy (1.3%).…”
Section: Anticoagulation During Open Surgery and Reconstructive Urolomentioning
confidence: 81%
“…Twelve studies investigated the association between BMI and RC outcomes [33][34][35][36][37][38][39][40][41][42][43][44] . Reyes et al 33 found that tract infections, pyelonephritis, wound infections and overall complications were less frequent in normal-weight patients (18.5-24.9kg/m 2 ) compared to overweight (25-29.9kg/m 2 ) and obese (≥30.0kg/m 2 ) patients.…”
Section: Body Mass Indexmentioning
confidence: 99%
“…BMI was not a predictor of mortality and complication development after RC in the Maurer et al 35 study, except for postoperative bleeding, which was more frequent in subjects with a high BMI. Compared to subjects with a BMI of 18-25kg/m 2 , subjects with a BMI >30kg/m 2 had a higher risk of cancer-specific mortality 38,42 , incisional hernia 40 , re-admission 30d and 90d after RC 39 , ileus 36 , parastomal hernia 45 and deep venous thrombosis 43,44 .…”
Section: Body Mass Indexmentioning
confidence: 99%